2023
DOI: 10.1172/jci.insight.157421
|View full text |Cite
|
Sign up to set email alerts
|

Low c-Kit expression identifies primitive, therapy-resistant CML stem cells

Abstract: Despite the efficacy of tyrosine kinase inhibitors (TKIs) in chronic myeloid leukemia (CML), malignant long-term hematopoietic stem cells (LT-HSC) persist as a source of relapse. However, LT-HSC are heterogenous and the most primitive, drug-resistant LT-HSC subpopulations are not well characterized.In normal hematopoiesis, self-renewal and long-term reconstitution capacity is enriched within LT-HSCs with low c-Kit expression (c-KIT Low ). Here, using a transgenic CML mouse model, we found that long-term engraf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The substantial treatment-induced changes observed within the stem cell population suggested that BCR::ABL1 + LSCs are themselves heterogeneous in terms of sensitivity to TKIs allowing us to define BCR::ABL1 + Lin − CD34 + CD38 −/low CD45RA − cKIT − CD26 + as the most TKI-insensitive cells. Apart from being detected at diagnosis, these cells are strikingly enriched after TKI therapy (Warfvinge et al, 2017), a finding since confirmed in a transgenic mouse model (Shah et al, 2023), and in clinical observations documenting long-term persistence of CD26 + cells in CML patients (Pacelli et al, 2023). Together, these findings argue that functional heterogeneity within LSCs cannot be predicted solely by surface markers but is intimately linked to their cell state and gene expression signature, thereby motivating a strategy to simultaneously capture their lineage potency/affiliation, BCR::ABL1 status, and molecular program in addition to the surface markers.…”
Section: Introductionmentioning
confidence: 84%
“…The substantial treatment-induced changes observed within the stem cell population suggested that BCR::ABL1 + LSCs are themselves heterogeneous in terms of sensitivity to TKIs allowing us to define BCR::ABL1 + Lin − CD34 + CD38 −/low CD45RA − cKIT − CD26 + as the most TKI-insensitive cells. Apart from being detected at diagnosis, these cells are strikingly enriched after TKI therapy (Warfvinge et al, 2017), a finding since confirmed in a transgenic mouse model (Shah et al, 2023), and in clinical observations documenting long-term persistence of CD26 + cells in CML patients (Pacelli et al, 2023). Together, these findings argue that functional heterogeneity within LSCs cannot be predicted solely by surface markers but is intimately linked to their cell state and gene expression signature, thereby motivating a strategy to simultaneously capture their lineage potency/affiliation, BCR::ABL1 status, and molecular program in addition to the surface markers.…”
Section: Introductionmentioning
confidence: 84%
“…In the latter, c-KIT is absent in the endothelial nucleus, while barely detectable at the endothelial cell membrane. It is noteworthy that in chronic myeloid leukemia, therapy-resistant hemopoietic stem cells responsible for the disease relapse and drug-resistance have been identified by a low c-KIT expression and pose a challenge to the efficacy of tyrosine kinase inhibitor-based therapies [69].…”
Section: The Dual Nuclear and Cell Membrane Endothelial C-kit Protein...mentioning
confidence: 99%